High temperature thermomechanical treatment of chromium-nickel steel - Azimova, Lala; V.F. Gahramanov; G.M. Huseynova; I.H. Hamdullayev (My University, 2025)
Among the methods of increasing the strength of steels, the methods of deformation of martensite based on mixing of deformation and heat treatment in various sequences has become widespread. The essence of this methods is that the hardening of the operation takes place at the end, and not before the martensitic transformation. This is most often done after quenching and low tempering, especially in the case of medium and high carbon steels.
Keywords: Steel; Chrome; Nickel; Processing; Structure